Alkaline dip DNA extraction from skin mucus for high-throughput sexing of sterlets (Acipenser ruthenus) - Kinami, Ryuhei (BioTechniques, 2025)
Studies on simple DNA extraction methods from fish mucus, which is an ideal resource for noninvasive sampling, are scarce. In the aquaculture of sturgeons such as sterlets (Acipenser ruthenus), a high-throughput genetic sexing method is needed, as only females are reared to maturity for their roe. Here, DNA extraction methods using HotSHOT (hot sodium hydroxide and tris), a novel alkaline dip, alkaline glycol, and water were compared using the skin mucus of sterlets (n = 8) collected with a toothpick. High-throughput sexing of sterlets from six production batches (n = 3953) was also evaluated using HotSHOT or alkaline dip. An alkaline dip with 10-25 mM NaOH was an effective alternative to HotSHOT, eliminating the heating and neutralizing steps. Regarding high-throughput sexing, > 99% (3946) individuals were successfully genotyped on the first PCR trial, and genotype ratios of each batch were close to 1:1, showing applicability of the alkaline dip method for practical sterlet sexing